Analysis Spoof Text Production Ability of Class XI High School Students with Problem-Based Learning (PBL) Approach - Evi Safitri Yulandari; Hendra Suryadi (Universitas Pendidikan Mandalika, 2022)
There are 13 types of texts in English, but English teachers rarely teach spoof texts because most teachers are more focused on descriptive text, procedure text, etc. So, students' understanding of spoof texts was very low, even most students don’t know what the spoof text is, and they are not accustomed to producing texts. The Problem Based Learning approach was chosen to make it easier for teachers to help students produce texts. Therefore, this present study aims to analyze students’ abilities in producing spoof texts by using a problem-based learning approach. This research used qualitative descriptive and selected class XI students as a sample of this research. Data collection in this study used the following instruments: observation, interviews, and questionnaires to analyze the data in descriptive qualitative form. Based on the results, this study can conclude that the level of students’ ability to produce spoof texts after applying the Problem Based Learning Approach at the post-test is a complete category. It was proved that an average score of 73.9 and the highest score of 86. The percentage test of students' completeness was 78%, i.e., 14 of 22 students are included in the complete category. In comparison, 22% are not included in the complete category, meaning that students still need improvement.